Ecological typology of woody vegetation of the Starohut forest massif as a component of the restoration of disturbed ecotopes - Olena Tykhonova; Tatiana Marukha; Petro Rybalko; Serhii Butenko; Serhii Horbas (Наукові горизонти)
The study aimed to determine the typological structure of the Starohut forest massif within the Desniansko-Starohutskyi National Nature Park based on the Ukrainian school of forest typology by Alekseev-Pogrebnyak. The massif covers an area of 6,778.8 hectares. The following trophotopes were identified in the study area: bors, subors, and sugruds. Bors, consisting of pine communities with some birch, occupy dry and fresh hygrotopes on flat terrain, covering 1.8 hectares or 0.02% of the total forest area. Subors, comprising pine-oak communities with birch and aspen, are found in fresh, moist, damp, and swamp hygrotopes, covering 4,510.1 hectares or 66.53% of the territory. Sugruds, consisting of oak-pine-lindenmaple forests on plains and aspen-birch-linden-maple forests in depressions, cover 2,266.9 hectares or 33.44% of the Starohut forest massif. No gruds were identified. The study found that the primary forest-forming species in the national park is Pinus sylvestris, occupying 5,092.7 hectares. Betula pendula covers 1,207.1 hectares, Alnus glutinosa – 201.4 hectares, Picea abies – 111.5 hectares, and Quercus robur – 90.0 hectares. Other tree species are sparsely represented. In the protected area of the park, fresh subors and sugruds dominate, including a mixture of birch, black alder, and spruce over a total area of 1,181.1 hectares, along with moist pine-birch-alder-oak subors and sugruds covering 849.4 hectares. The recreational zone is dominated by fresh hygrotopes with subors and sugruds totalling 2,336.4 hectares. In the economic zone, subors and sugruds prevail on fresh sandy soils, totalling 430.7 hectares. The results support the restoration of natural forest types in areas affected by large-scale fires in 2023-2024 and other anthropogenic influences